Greenhouse gas sources and mitigation strategies from a geosciences perspective - Daniel J. Soeder (Yandy Scientific Press, 2021)
Certain gases that are capable of trapping heat in the Earth’s atmosphere are known as “greenhouse gas” and are important for helping to regulate temperature. Major greenhouse gases include carbon dioxide, methane, water vapor, chloroﬂuorocarbons, and nitrous oxide. Burning fossil fuels produces carbon dioxide as a combustion product and atmospheric concentrations have increased dramatically over the past two centuries. The heat trapped by this additional greenhouse gas is changing climates, melting ice sheets and glaciers in polar regions, raising sea levels, and affecting ocean currents. Climate change can be mitigated by preventing the emission of additional fossil fuel combustion products to the atmosphere and reducing existing greenhouse gas levels back to pre-industrial revolution concentrations. This requires switching energy production to sustainable, non-fossil sources and applying carbon capture, use, and storage technology on the fossil fuel combustion that remains. The implementation of direct air capture technology to reduce existing carbon dioxide levels in the atmosphere can further remediate climate impacts. Captured carbon dioxide can be stored in plant tissues, soils, deep underground in geological repositories, or as solid materials like concrete or carbonates to keep it from reentering the atmosphere. Although non-carbon energy sources have recently become more cost-competitive with fossil energy, technological advancements and government policies are still needed to overcome the inherent economic advantages of fossil fuels. A global strategy must be developed to convince people that the higher cost of clean, sustainable energy is a price worth paying to replace fossil fuels and prevent a major environmental calamity.